Coping behavior of convicts: towards the potential of social identity theory - D.V. Melnikova; I.B. Bovina; M.G. Debolsky (Психология и право, 2025)
The focus of our attention in this paper is to discuss the coping behavior of inmates and to consider the potential of applying social identity theory to understanding this phenomenon. Coping behavior is a multidimensional phenomenon that can be defined as conscious behavior aimed at active interaction with a stressful or difficult life situation, i.e. changing it (when it is controllable) or adapting to it (when the situation is uncontrollable). Under social identity we understand an individual's knowledge of his/her belonging to certain social groups together with some emotional and value significance of this group membership for him/her. Having considered the main foreign and domestic approaches to understanding the coping behavior, as well as some provisions of the theory of social identity, we can make a key conclusion that it is important to consider the coping behavior of convicts not only at the individual, but also at the social level. The main thesis discussed in the framework of this theoretical and analytical work is the idea that the content of coping behaviors in a difficult life situation is, among other things, determined by the orientation of social groups in which a person is included. Due to the fact that such groups can have antisocial orientation, the study of the characteristics of a person's social identities and the degree of identification with this or that group becomes especially relevant, since, being a member of a social group, a person's coping behavior in a difficult life situation is determined by the orientation of social groups.